Basic Electrical Installation Work - Linsley, Trevor (Oxford : Newnes, 2005)
This textbook on electrical installation covers all aspects of the City and Guilds Part 1 syllabus and amendments to the 16th IEE regulations, and includes sections on quality assurance, customer care and legislation.
Previous ed.: London: Arnold, 1998.
Includes index.
Keywords: Electric apparatus and appliances -- Installation; Electric apparatus and appliances -- Installation -- Standards; Electric wiring, Interior; Technology